Isolated Gastric Perforation following Blunt Trauma Abdomen not to be Missed: A Case Series - Verma, Surender; Bansal, Anand Rai; Verma, Anjali; Garg, Pradeep; Yadav, Sunil Kumar; Kumar, Dinesh; Goel, Shubham (Asian Journal of Medical Sciences, 2024)
Abdominal trauma is a commonly encountered emergency which may be because of roadside accidents, assaults, or falls from height. Blunt injury to the abdomen is far more common than penetrating injury. Gastric perforation commonly occurs following penetrating abdominal trauma. However, gastric rupture is an uncommon entity following blunt trauma abdomen (BTA). Here, we are presenting three cases of isolated gastric perforation after BTA, two were due to a roadside accident, and one was a result of a fall from height. History suggests of a full stomach is usually found in traumatic gastric rupture. This condition usually presents with insignificant clinical or radiological signs. Isolated gastric rupture due to trauma is rare as it is usually associated with other injuries such as splenic and liver injuries. Early suspicion plays an important role in diagnosing this entity which carries higher morbidity and mortality if not managed timely. As isolated gastric perforation because of trauma leads to high morbidity and mortality, hence thorough lavage of the peritoneal cavity followed by double-layer closure after adequate debridement will reduce chances of intraperitoneal contamination thus improving outcome. Presentation after the last meal, the severity of gastric rupture, and other associated injuries play an important role in the prognosis of the patient.